Bioelectrical impedance analysis versus reference methods in the assessment of body composition in athletes - Campa, F.; Gobbo, L. A.; Stagi, S.; Cyrino, L. T.; Toselli, S.; Marini, E.; Coratella, G. (European Journal of Applied Physiology, 2022)
The present systematic review aimed to compare the accuracy of Bioelectrical Impedance Analysis (BIA) and Bioelectrical Impedance Vector Analysis (BIVA) vs. reference methods for the assessment of body composition in athletes. Studies were identified based on a systematic search of internationally electronic databases (PubMed and Scopus) and hand searching of the reference lists of the included studies. In total, 42 studies published between 1988 and 2021 were included. The methodological quality was assessed using the Quality Assessment Tool for Observational Cohort and Cross-sectional Studies as recommended by the National Institute of Health. Twenty-three studies had an overall good rating in terms of quality, while 13 were rated as fair and 6 as poor, resulting in a low to moderate risk of bias. Fat mass was inconsistently determined using BIA vs. the reference methods, regardless of the BIA-technology. When using the foot to hand technology with predictive equations for athletes, a good agreement between BIA and the reference methods was observed for fat-free mass, total body, intra and extra cellular water. However, an underestimation in fat-free mass and body fluids was found when using generalized predictive equations. Classic and Specific BIVA represented a valid approach for assessing body fluids (Classic BIVA) and percentage of fat mass (Specific BIVA). The present systematic review suggests that BIA and BIVA can be used for assessing body composition in athletes, provided that foot-to-hand technology, predictive equations, and BIVA references for athletes are used.